After intra-EU BITs and the ECT, the EU needs to abandon extra-EU BITs: For legal, energy and climate policy, and political economy reasons - Martin Dietrich Brauch; Stefan Mayr; Carl Frederick Luthin (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
After terminating intra-EU bilateral investment treaties (BITs) and withdrawing from the Energy Charter Treaty, the EU and its member states should terminate BITs with extra-EU partners. Extra-EU BITs risk undermining the autonomy of EU law, hinder EU energy and climate goals, and fail to establish balanced sustainable investment partnerships.
Keywords: 330